Using a threaded framework to enable practical activities in Operating Systems courses - Manacero, Aleardo [UNESP] (2013)
Teaching Operating Systems (OS) is a rather hard task, since being an OS designer is not a desired goal for most students and the subject demands a large amount of knowledge over system's details. To reduce the difficulty many courses are planned with laboratory practices, differing in how the practices are designed. Some try to implement next-to-real kernels, others use simulators, and even others use synthetic kernels. In this paper an approach based on synthetic kernels is described. It uses thread programming in order to establish control over the operating system components. T his approach allows the kernel to grow following the materials presented in the course. It has been successfully applied in two different courses at our University, the first one being a basic OS course and the second one an upper level course. Results from these applications are presented.